THE SIMILARITIES AND DIFFERENCES OF PROVERBS WITH OTHER GENRES - Boltayevna, Ikromova Lola; Nabiyevna, Nabiyeva Zarina; Ixtiyorovna, Rasulova Muhabbat (International Journal of Psychosocial Rehabilitation, 2020)
The proverbs are the cultural heritage of the people. It reflects all the thoughts, worldviews, lifestyles, character and beliefs of the people. Since each nation has its own characteristics, it does not affect on their proverbs. Even though the topics in the proverbs are similar, their images are unique. These images provide the national color of the proverbs.In analyzing linguocultural aspects of Uzbek and English proverbs, it is important to note that the language and culture of both peoples are interrelated. In this article, some of the proverbs are analyzed linguoculturologically and revealed their peculiarities, sometimes with the same or sometimes totally different expressions. In this case, the English and Uzbek proverbs reflected in all Uzbek and English traditions, from the past to the present day, and the proverbs in this article are examples of folklore. In examining the mentality of the Uzbek and English people, the Uzbek and English proverbs can highlight the similarities and differences between the two nations.By analyzing the Uzbek and English folklore in a thematic manner, we conclude that all the proverbs in Uzbek can be found in English folklore. It is possible to find the equivalent proverbs in both languages on the same topic.